1988
DOI: 10.1007/bf01560565
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial meningiomas in the elderly (over 70 years old)

Abstract: The decision to operate on a patient older than 70 years for an intracranial meningioma is always difficult. Therefore a series of meningiomas treated surgically in 30 cases older than 70 years has been reconsidered and studied according to the following parameters: Karnofsky's rating scale, physiological status of the patient (A.S.A. criteria), perifocal oedema and mass effect. The locations of the meningiomas were: convexity 13, parasagittal 6, falx 2, pterion (sphenoid ridge) 5, orbito-cranial 3, jugum sphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
3

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(41 citation statements)
references
References 6 publications
3
35
0
3
Order By: Relevance
“…8,9,11,13,20 However, patients with exceptional surgical risk factors such as advanced age, poor functional status, and strategic tumor locations are considered poor candidates for surgery which aims for complete tumor resection. 12,14,15 Subtotal resection, which carries significant morbidity and mortality for poor risk patients, offers much worse LC, which was on the order of 40% at five years. 3,8,9 Mirimanoff et al 11 reported a 10-year progressionfree survival of 80% for patients who had a complete resection for benign meningioma compared to only 45% for those who had subtotal resection in a series of 225 patients.…”
Section: Surgical Resectionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9,11,13,20 However, patients with exceptional surgical risk factors such as advanced age, poor functional status, and strategic tumor locations are considered poor candidates for surgery which aims for complete tumor resection. 12,14,15 Subtotal resection, which carries significant morbidity and mortality for poor risk patients, offers much worse LC, which was on the order of 40% at five years. 3,8,9 Mirimanoff et al 11 reported a 10-year progressionfree survival of 80% for patients who had a complete resection for benign meningioma compared to only 45% for those who had subtotal resection in a series of 225 patients.…”
Section: Surgical Resectionmentioning
confidence: 99%
“…[9][10][11] However, meningiomas may recur after surgery and curative resection can result in significant morbidity because of strategic tumor location and old age. [12][13][14][15] Stereotactic radiosurgery (SRS) can deliver a single high dose of radiation to a localized area in the brain for the treatment of meningiomas that are unresectable, recurrent or residual after surgery. However, large tumors and tumors adjacent to vital ABSTRACT: Objective: To evaluate the safety and efficacy of stereotactic radiosurgery (SRS) compared to fractionated stereotactic radiation therapy (FSRT) for meningiomas treated over a seven year period.…”
mentioning
confidence: 99%
“…Our 6-month mortality rate (20%) is higher than most reported rates (7-19.3%). [5][6][7][8]10,11,18 Four of the deaths recorded in the present study were due to brain swelling and rostro-caudal herniation during the first 1-2 weeks of surgery. All the patients presented after 3 years of onset (considered as late presentation) with signs and symptoms of raised intracranial pressure and, on CT, large tumours (>50 mm) bordered by grade 3 peritumoural oedema.…”
Section: Discussionmentioning
confidence: 99%
“…Of age, sex, tumour size, location, vascularity, oedema and histology, Alaywan and Sindou 8 found severity of preoperative neurological conditions and tumour size to be the only predictors of adverse outcome, including morbidity and mortality, and stressed the additional role of vascular supply from the pia mater. 9 Djindjian et al 10 also found that preoperative clinical status (including a Karnofsky rating of less than 50), peritumoural oedema and mass effect are essential parameters for quantifying surgical risk, while in the series of Meixensberger et al, 11 age, poor preoperative clinical condition (ASA [American Society of Anesthetists] score), intra-and postoperative bleeding and cerebrospinal fluid disturbances were significantly associated with a subsequent decrease of quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Though most meningiomas can be operated successfully, morbidity and mortality remain considerably high in some critical locations, and the recurrence rate may exceed expectation in some subgroups [2][3][4][5]. Gamma knife radiosurgery provides an excellent method for treatment of intracranial meningiomas, with a total tumor control rate between 92 and 100% in some reports, with tumor regression in 24-74%.…”
Section: Introductionmentioning
confidence: 99%